Analysis of traumatic acute diaphragmatic injuries - İlhan Taş; Ebral Yiğit (Singapore Medical Journal, 2025)
Introduction: Diaphragm rupture (DR) is a rare pathological event usually caused by trauma. We aimed to analyse the characteristics of acute diaphragmatic injuries due to trauma and the treatment of such injuries. Methods: This study included the data of 15 patients who sustained diaphragmatic injuries due to trauma and underwent surgery at the Diyarbakır Gazi Yaşargil Training and Research Hospital General Surgery Service between January 2016 and December 2019. Results: There were 240 patients who presented with abdominal trauma during the study period, and DR was detected in 15 (6.25%) of these patients. The male to female ratio was 14 to 1, and the average age of the patients was 29.66 ± 10.56 (15–46) years. The most common cause of diaphragmatic injury was penetrating abdominal injuries (86.7%). Blunt abdominal trauma accounted for 13.3% of the DR cases. Preoperative shock was present in four (26.7%) patients. Preoperative diagnosis was made in only one (6.7%) of 15 patients with DR. Other patients were diagnosed during operation. Thirteen (86.7%) patients had additional organ injuries, and two patients had isolated diaphragmatic injuries. The most frequently injured organ was the lung (n = 7, 46.6%). Complications developed in six patients (morbidity rate 40%), and pulmonary complications were most frequently encountered (n = 5, 33.3%). The mortality rate was 6.7%. Conclusion: As traumatic DRs are uncommon and often associated with additional organ injuries, a careful general assessment of the patient should be made.